Pest Control Technology for Plutella Xylostella L. on Green Mustard (Brassica Juncea L.) Using Bacillus Thuringiensis in Tukungan Soil - Akhmad Rizali; Riza Adrianoor Saputra; Muhammad Alfian (TROPICAL WETLAND JOURNAL, 2021)
Green mustard (Brassica juncea L.) is a popular vegetable among the people. Green mustard leaves are commonly used as complementary ingredients such as chicken noodle, meatballs, etc. These vegetables are easily accessible to traditional markets, supermarket, and mall. The main obstacle in cultivating green mustard is Plutella xylostella attack. P. xylostella pests can attack both vegetative and generative, striking at the shoots and leaves of plants from breeding to harvesting. One of the effective and safe controls is the bioinsecticide Bacillus thuringiensis. Tukungan soil is a swamp land management technology that aims to diversify commodities that can be planted. This technology is very helpful in utilizing and maximizing existing agricultural land, especially in South Kalimantan. The bioinsecticide material used is a strain of B. thuringiensis which is the Turex WP. This research aims to determine the best dose of bioinsecticide B. thuringiensis (Turex WP) in controlling P. xylostella pests, increasing growth and yield of green mustard in tukungan soils. The research used a one-factor randomized block design, namely the dose of bioinsecticide (Turex WP) consisting of five treatments: p0 = 0 g/L, p1 = 0.5 g/L, p2 = 1 g/L, p3 = 1.5 g/L, and p4 = 2g/L. The results showed that the bioinsecticide B. thuringiensis (Turex WP) with a dose of 2 g/L was effective in controlling P. xylostella pests, increasing growth and yield of green mustard in tukungan soils.